Cultural conditioning of employees' engagement = Kulturowe uwarunkowania zaangażowania pracowników - Stankiewicz, Janina; Moczulska, Marta (Zielona Góra: Faculty of Economics and Management Press)
The article presents the problem of employees' engagement. Being aware that values are the basis of employees' engagement it was assumed that it could be different in enterprises operating in diverse cultures. Taking the models of culture by G. Hofstede and H. Schwarz into consideration as well as factors influencing engagement the analysis of cultural conditioning of engagement was conducted.
Keywords: zaangażowanie pracowników; kultura; uwarunkowania kulturowe; employee engagement; culture; cultural determinants